Cognitive impairment and the gut-brain axis during 2014–2023: a bibliometric analysis - He, Jindi; Wu, Jiaxun; Liu, Juan; Wu, Hangcai; Hua, Heliu (Frontiers in Neurology, 2024)
Background The burden on society grows as the number of individuals with cognitive impairment rises. Numerous research have discovered a connection between cognitive impairment and the gut-brain axis, which is useful in examining the pathophysiology of cognitive impairment and potential therapeutic approaches. As a result, this article explores developments and trends in the research concerning the gut-brain axis and cognitive impairment through a bibliometric analysis of the contributions made by various countries/regions, institutions, authors, and journals. Methods We looked for articles on gut-brain axis and cognitive impairment from 2014 to 2023 in the Web of Science Core Collection. For the descriptive analysis, figures and tables were taken using GraphPad Prism 6 and WPS Office 2024. For the visual analysis of the countries/regions, institutions, authors, and keywords, VOSviewer was utilized. Results We obtained 458 publications from 1 January 2014 to 9 September 2023. The country with the most publications (175, 38.21%) was China. The country with the greatest total number of citations (3,138, 17.22%) was the United States of America. The highest number of articles (15, 3.26%) was issued by Zhejiang University. The most published first author is Karsas M. In this field, Nutrients have published the most articles (24). The most often occurring keywords include “Alzheimer’s disease,” “cognitive impairment,” “gut microbiota,” “inflammation,” “diet,” etc. “Stroke,” “tau,” “probiotics,” “exercise,” “fecal microbiota transplantation,” etc. emerged later. Conclusion An increasing amount of research has focused on the connection between cognitive impairment and the gut-brain axis. In this area, the United States of America and China have both made significant contributions. The author team’s collaboration has to be improved. Our study contributes to understanding the field’s current state and predicting its future trend.